Relatório de Estágio Profissional "Na luta por um sonho: Ser Professora de Educação Física" - Geraldin Cristina Pereira Mendes (2019)
In this report, a set of experiences lived in the trajectory of the professional stage, experiences that occurred in the Basic and Secondary School Dr. Ângelo Augusto da Silva (EBSAAS), located in the Autonomous Region of Madeira, with the intention of obtaining the degree Master's degree in Teaching Physical Education in Basic and Secondary Education, at the Faculty of Sport of the University of Porto (FADEUP).This internship had the supervision and monitoring of a teacher from FADEUP, as well as a cooperative teacher from EBSAAS, both with a vast experience in the act of teaching sports modalities. In this report, it is possible to find three main themes, where the first one, has a personnel framework on which I give to know a little about me, highlighting the motivation for choosing this course and still my sports preferences. On the second theme, i will discuss the institutional framework where the mission, vision and the sports facilities present at EBSAAS are mentioned, as is approached and demonstrated my core of internship and the characterization of my resident class. Lastly on the third theme is present, the operational framework, where within this subject is patent three large Areas. In Area 1 is the organization and management of teaching and learning, with conception, realization and reflections. In Area 2, participation in the school and the relationship with the community, such as non- academic activities, assisted meeting and the passage through the Secondary. In Area 3, is the professional development with an investigation-action which addresses the theme of the difficulty to integrate students with special educational needs and strategies used for this integration in the class and in the exercises exclusively applied to the professor of Physical Education in EBSAAS.